Multidrug-Resistant Tuberculosis Outbreak among US-bound Hmong Refugees, Thailand, 2005 - Oeltmann, John E.; Varma, Jay K.; Ortega, Luis; Liu, Yecai; O’Rourke, Thomas; Cano, Maria; Harrington, Theresa; Toney, Sean; Jones, Warren; Karuchit, Samart; Diem, Lois; Rienthong, Dhanida; et al. (Emerging infectious diseases, 2008)
In January 2005, tuberculosis (TB), including multidrug-resistant TB (MDR TB), was reported among Hmong refugees who were living in or had recently immigrated to the United States from a camp in Thailand. We investigated TB and drug resistance, enhanced TB screenings, and expanded treatment capacity in the camp. In February 2005, 272 patients with TB (24 MDR TB) remained in the camp. Among 17 MDR TB patients interviewed, 13 were found to be linked socially. Of 23 MDR TB isolates genotyped, 20 were similar according to 3 molecular typing methods. Before enhanced screening was implemented, 46 TB cases (6 MDR TB) were diagnosed in the United States among 9,455 resettled refugees. After enhanced screening had begun, only 4 TB cases (1 MDR TB), were found among 5,705 resettled refugees. An MDR TB outbreak among US-bound refugees led to importation of disease; enhanced pre-immigration TB screening and treatment decreased subsequent importation.